Imaging in Juvenile Idiopathic Arthritis: A Comprehensive Review - Stuti Chandola; Narendra Bagri; Manisha Jana (Indian Journal of Radiology and Imaging)
Juvenile idiopathic arthritis (JIA) is the most common rheumatological disorder of the pediatric age group and includes all forms of arthritis that commence within 16 years of age, last for more than 6 weeks, and are of unknown cause. Its diagnosis is mainly clinical; however, imaging is essential in cases of equivocal clinical diagnosis, evaluation of disease burden, disease activity, and joint damage. Although radiographs were being used conventionally in JIA, the advent of anti-inflammatory therapies in JIA has resulted in a paradigm shift to increased utilization of ultrasonography and magnetic resonance imaging in disease evaluation, owing to greater sensitivity of the two modalities for detection of early inflammatory stages of the disease. This review discusses the role of imaging in JIA, including salient imaging findings and available scoring systems for monitoring this entity.